Calculations of electron scattering from cadmium - Berrington, Michael; Bostock, Christopher; Fursa, Dmitry; Bray, Igor; McEachran, R.; Stauffer, A. (American Physical Society, 2012)
Electron scattering from the ground state of cadmium atoms has been investigated theoretically using the convergent close-coupling, relativistic convergent close-coupling, relativistic optical potential, and relativistic distorted-wave methods. Elastic and inelastic differential cross sections, Stokes parameters, and spin-asymmetry parameters have been calculated and compared with available experimental and theoretical results. We find, in general, very good agreement between the theories and experiment.